Graphene oxide functionalization as friction modifier additives for lube oil / Nurul Athirah Ismail - Nurul Athirah, Ismail (2017)
Nowadays, increasing transportation activities have consumed much of our energy resources day by day, and a significant portion of the energy produced is spent on overcoming friction in moving mechanical systems. Lubricant additive is one of the technologies that can be used to reduce friction. Therefore, it is expected that the demand and consumption of additives will increase. To lubricate moving mechanical systems, lube oil is required. However, base oil itself is not good enough to act as a lubricant in reducing friction. Addition of additives to base oil are required to provide excellent lubrication. The modification of graphene oxide (GO) as a friction modifier additive is proposed to improve lube oil lubrication in moving mechanical systems. In recent studies, graphene is indicated as a two-dimensional material which offer unique friction and wear properties that are not typically seen in conventional materials. According to its structure, GO consists of several oxygen functional groups. In general, the hydroxyl (OH) group can be found on the surface of GO and carboxylic (COOH) group found at the edges. However, inorganic nanoparticles can agglomerate easily, hence their dispersive ability is very poor in organic solvents and oil. The agglomeration of GO in the base oil will occur especially at high temperatures. Therefore, various chemical modifications of GO has been studied, to change its surface properties in order to have a well-dispersed GO in the base oil. The introduction of organic moiety on the surface of the GO is expected to increase its dispersibility in oil. Therefore, this study focuses on the synthesis of GO materials through the oxidation of graphite powder. This step was continued with the functionalization of GO that has been carried out by introducing alkyne-functionalized GO, GOf and azide-functionalized alkyl, N3R via click chemistry as a dispersing agent. The modified GO was then introduced into base oil at different compositions. The obtained reduced functionalized graphene oxide (rGOf) materials were then further studied in terms of its properties as lubricating oil in moving mechanical systems.